Response to mason and drakeman's commentary on "fishing for sharks: Partner selection in biopharmaceutical R&D alliances". (8th May 2014) - Diestre, Luis; Rajagopalan, Nandini
<x xml:space="preserve">Abstract</x> We respond to Mason and Drakeman's comment on our published paper titled "Are All 'Sharks' Dangerous? New Biotechnology Ventures and Partner Selection in R&D Alliances" (Diestre and Rajagopalan, 2012). We discuss both their survey analysis and alternative explanation and conclude that neither of them invalidates our theoretical premise and our empirical conclusions. Copyright © 2014 John Wiley & Sons, Ltd.